Cumulative damage analysis and experimental investigation of transmission tower structures under sequential seismic excitations - Pingping Nie; Haiqing Liu; Saiyu Shao; Zhiwen Yang; Jingrui Li; Siyi He (Soil Dynamics and Earthquake Engineering, 2026)

The recent process and functional applications of inkjet printing in organic solar cells - Shaomeng Li; Pingping Yang; Miaomiao Zhang; Ziwei Zhao; Zhanwei He; Wenxuan Lv; Haining Chen; Qixian Zhang; Mangmang Gao (Chemical Engineering Journal, 2026)

Epigenetic Regulation of Gill Function in Japanese Flounder Under Hypoxic Stress Analyzed via Genome-Wide Methylome and Transcriptome Dynamics - Hengtai Tang; Chengnan Ding; Tianyang Cai; Guangling Li; Pingping Liu; Zhirui Zhang; Feng He (Journal of Ocean University of China, 2026)

Cold plasma technology for the modification and quality control of food components via exogenous RONS: Mechanisms, strategies, and future prospects - Xiaotong Fan; Jiabao Ni; Yanxiang Bi; Shiye Luo; Pingping Dong; Shenyuan Quan; Jiaxin He; Xiaoming Fang (Food Bioscience, 2026)

Morphology, molecular identification, and pathogenicity of two Alternaria species associated with leaf spot of common bistort (Bistorta officinalis Delarbre) in China - Lin He; Jie Zhao; Jianxin Deng; Shanghua Liu; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Isolation and identification of two causal agents associated with root rot of Scutellaria baicalensis - Lin He; Qianci Chen; Pingping Sun; Lei Zhang; Honghong Jiao; Hongmei Cui; Yuan Yuan; Zhengnan Li (Physiological and Molecular Plant Pathology, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Light engineering in aquaculture: physiological responses of Takifugu rubripes larvae to controlled LED irradiance - Xin Li; Songtao Liu; Yafang Liu; Pingping Wei; Yanling Wu; Yingying Fang; Fei Sun; Ying Liu; Yumeng Wu; He Ma (Frontiers in Marine Science, 2026)
Introduction While indoor aquaculture has expanded globally, optimal lighting strategies for fish growth remain understudied. This study aims to establish optimal LED protocols for indoor-reared Takifugu rubripes larvae. Methods T. rubripes larvae were maintained at 50, 250, 500, and 750 mW/m 2 (i50, i250, i500, i750) from hatching through 30 DPH. Growth, gene expression, and enzyme activities were measured. Results Positive growth effects were observed at i250 and i500 within 14–17 DPH, while i50 caused complete mortality after 21 DPH. At 20 DPH, i500 upregulated IGF-1 and BMP2 expression, whereas i50 downregulated BMP4 and SOX9. i50 elevated CTSF, IGM, and HSP70, indicating stress. LPS activity was highest in i250 at 15 DPH, while LDH was lowest in i50. From 10–20 DPH, AKP and ACP were consistently lower in i50. During 5–20 DPH, SOD was suppressed in i750, while T-AOC increased in i250. Discussion Light conditions critically modulate enzymatic activity and early growth in T. rubripes larvae, though underlying mechanisms require further investigation.

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

18–26 years: A critical window for synergistic reduction of atmospheric pollutant and greenhouse gas emissions - Pingping Song; Zhenhui Gao; Zhiyuan Duan; Junhua Song; Haiyan Duan; Siyan Chen; Bailin He; Meng Gao (Environmental Impact Assessment Review, 2026)

Event- and annual-scale precipitation extremes enhance groundwater recharge at the ecological restoration catchment of hilly and gully region - Meina He; Yunqiang Wang; Yali Zhao; Li Wang; Ziliang Zhang; Yi Song; Pingping Zhang; Zimin Li (Ecological Engineering, 2026)

Reinforced π-conjugated organosulfur PDI polymer boosting peroxymonosulfate activation for photocatalytic degradation of bisphenol A - Pingping Lu; Qiuyi Ji; Xiaoqian Ye; Guanshun Wang; Yangbo Cheng; Wendi Zhou; Zhe Xu; Gancheng Zuo; Xin Jin; Guoyang Zhang; Limin Zhang; Huan He (Chemical Engineering Journal, 2026)

Long-term monitoring reveals scale-dependent decoupling of waterbird diversity at a tropical island flyway node - Miaomiao He; Yufeng Lin; Cheng Cheng; Zhiqin Zhou; Pingping Guo; Xin Fan; Wenqing Wang (Journal of Environmental Management, 2025)

Ionic covalent organic framework nanosheets modulated polyamide membranes for augmented ion sieving - Rui Li; Meng He; Shuangqiao Han; Linze Li; Pingping Chen; Xiao Wang; Yuping Tong; Jingli Gong; Huixian Wang; Yatao Zhang; Junyong Zhu (Desalination, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Selective breeding boosts oyster resilience to ocean acidification via energy budget modulation - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Nitrogen-doped porous carbon derived from MIL-88-NH2 precursors for sulfur cathode of Na S batteries - Mei Yang; Qiuyang Ma; Hengli He; Jiaqi Zhang; Shanshan Zhu; Xuanming Chang; Luzhou Zhang; Pingping Zhou; Zhong Wu; Guilin Zhuang; Zhen Fang (Chemical Engineering Journal, 2025)

Mechanisms of aristolochic acid I Hepatotoxicity: Central role of PDK4-Induced mitochondrial dysfunction and hepatic inflammation - Zhaobin Wang; Kunyang Li; Xiaoqi Yi; Yichen Wu; Yang Zhao; Pingping He; Qinghua Zeng; Enxiang Zhang (Food and Chemical Toxicology, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

Evaluation of pear orchard yield and water use efficiency at the field scale by assimilating remotely sensed LAI and SM into the WOFOST model - Liang Jiang; Feilong Zhang; Jianan Chi; Pingping Yan; Xiangxin Bu; Yong He; Tiecheng Bai (Computers and Electronics in Agriculture, 2025)

6:2 fluorotelomer sulfonate as a safer alternative to PFOS: Comparative cytotoxicity and oxidative stress mechanisms in pancreatic β-cells (INS-1 model) - Xiao-Min Ren; Jianying Wang; Fenqing Zhao; Pingping Zhang; Zhenghuan Zhang; Zhongneng Yang; Huan He; Zhixiang Xu; Bin Huang; Xuejun Pan (Toxicology in Vitro, 2025)

The capsid protein p72 specific mAb and the corresponding novel epitope based ELISAs for detection of ASFV infection - Jiajia Zhang; Ziyan Sun; Shaohua Sun; Kaili Zhang; Dafu Deng; Ping He; Pingping Zhang; Nengwen Xia; Sen Jiang; Wanglong Zheng; Francois Meurens; Jianzhong Zhu (Veterinary Microbiology, 2025)

A nucleocapsid monoclonal antibody based sandwich ELISA for the general detection of both PRRSV-2 and PRRSV-1 - Shaohua Sun; Kaili Zhang; Jiajia Zhang; Ping He; Pingping Zhang; Dafu Deng; Chenglin Chi; Sen Jiang; Wanglong Zheng; Nanhua Chen; Jianzhong Zhu (Veterinary Microbiology, 2025)

Preparation of pitch-based carbon fiber from medium coal tar pitch refined by wash oil - Pingping Zuo; Shaobo Fu; Xiaoqiang He; Hongxian Niu; Shijie Qu; Wenzhong Shen (Fuel, 2025)

Fe, N-CQDs triggered the fabrication of alginate encapsulated g-C3N4 hydrogel for efficient photocatalytic activation of PMS and antibiotic degradation - Haiyan Yang; Xiao Cao; Yiyang He; Xinchao Zhang; Pingping Zhang; Xin Wang; Yuehong Liu; Suyun Xu; Yuyin Fang; Lin Gu (Carbohydrate Polymers, 2025)

Corrigendum to “Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves” [Mar. Environ. Res. 204 (2025) 106871] - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Boosting lactic acid photocatalytic synthesis from biomass sugars: The synergistic effect of N-doped carbon dots on ultrathin carbon nitride - Xiao Cao; Xin Wang; Yiyang He; Jixin Li; Haiyan Yang; Pingping Zhang; Songrui Yang; Haixiang Yu; Suyun Xu; Haiping Yuan; Lin Gu (Food Chemistry, 2025)

Satellite navigation signal quality monitoring algorithm based on DBO-SVM - Ershen Wang; Yilin He; Tengli Yu; Liang Liu; Song Xu; Pingping Qu; Tao Pang (Advances in Space Research, 2024)

Exploring the environmental influences and community assembly processes of bacterioplankton in a subtropical coastal system: Insights from the Beibu Gulf in China - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Yusen Li; Wenjian Chen; Zelong Zhao; Linyuan Jiang; Lei Zhou (Environmental Research, 2024)

Resveratrol Ameliorates Retinal Ischemia-Reperfusion Injury by Modulating the NLRP3 Inflammasome and Keap1/Nrf2/HO-1 Signaling Pathway - Jiazhen Feng; Kaibao Ji; Yiji Pan; Pingping Huang; Tao He; Yiqiao Xing (Molecular Neurobiology, 2024)

Inversion of coastal cultivated soil salt content based on multi-source spectra and environmental variables - Pingping Jia; Wei He; Yi Hu; Yanning Liang; Yinku Liang; Lihua Xue; Kazem Zamanian; Xiaoning Zhao (Soil and Tillage Research, 2024)

Seasonal dynamics of antibiotic resistance genes and mobile genetic elements in a subtropical coastal ecosystem: Implications for environmental health risks - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Wei Li; Yusi Zheng; Yusen Li; et al. (Environmental Research, 2024)

Corrigendum to “Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus” [Veterin. Microbiol. 276 (2023) 109615] - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2024)

An integrated simulation-optimization approach for combined allocation of water quantity and quality under multiple uncertainties - Yaping Huang; Yanpeng Cai; Chao Dai; Yanhu He; Hang Wan; Hongjiang Guo; Pingping Zhang (Journal of Environmental Management, 2024)

Association Between Circulating Zinc Levels and Risk Factors of Metabolic Syndrome: Insights from a Bi-directional Mendelian Randomization Analysis and Cross-Sectional Study - Yuanyuan Wu; Guoqiong Xu; Ruixue Bai; Pingping Yu; Zhongxiang He; Mengxue Chen; Yukun Hu; Tao Jiang; Yuanhang Yang; Dongfang Liu; Ying Mei; Xiaoya Qi; et al. (Biological Trace Element Research, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Response of deep soil water deficit to afforestation, soil depth, and precipitation gradient - Jingxiong Zhou; Yunqiang Wang; Ruijie Li; Haoran He; Hui Sun; Zixuan Zhou; Yali Zhao; Pingping Zhang; Zimin Li (Agricultural and Forest Meteorology, 2024)

Sulforaphane inhibits the migration and invasion of BPDE-induced lung adenocarcinoma cells by regulating NLRP12 - Wei Wang; Shufan Chang; Xi He; XiaoLei Zhou; Pingping Shang; Yusong Chen; Xiaoke Wang; Lijuan Chen; Qiao Zhang; Yahong Qiao; Feifei Feng (Toxicology and Applied Pharmacology, 2024)

Mechanistic insights into the adsorption and extraction of rare earth ions using oxygen- and phosphorus-doped porous graphitic carbon nitride - Yiping Feng; Pingping Chen; Xingye Lian; Chenyi He; Chaoyu Zheng; Haijian Lu; Longyong Lin; Guoguang Liu; Yirong Deng (Journal of Environmental Chemical Engineering, 2024)

Changing soil available substrate primarily caused by fertilization management contributed more to soil respiration temperature sensitivity than microbial community thermal adaptation - Zhibin Guo; Chang-An Liu; Keke Hua; Daozhong Wang; Pingping Wu; Shuixia Wan; Chuanlong He; Linchuan Zhan; Ji Wu (Science of The Total Environment, 2024)

NtERF4 promotes the biosynthesis of chlorogenic acid and flavonoids by targeting PAL genes in Nicotiana tabacum - Shun He; Xin Xu; Qian Gao; Changjun Huang; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Haitao Huang; Jun Yang; Jianmin Zeng; Zhong Wang (Planta, 2024)

Historical and comparative overview of sponge campus construction and future challenges - Pingping Luo; Peiyao Yan; Xiaohui Wang; Yang Wu; Jiqiang Lyu; Bin He; Weili Duan; Shuangtao Wang; Xianbao Zha (Science of The Total Environment, 2024)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

The transcription factor NtERF13a enhances abiotic stress tolerance and phenylpropanoid compounds biosynthesis in tobacco - Zhong Wang; Jinchu Yang; Qian Gao; Shun He; Yongming Xu; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Xin Xu; Lanxin Ma; Zhan Zhang; Yongfeng Yang; et al. (Plant Science, 2023)

NIR-II photo-amplified peroxidase-like activity using biocatalytic copper-based nanoplatform against subcutaneous methicillin-resistant Staphylococcus aureus infection - Danyan Wang; Xiaojun He; Qiang Wang; Pingping Li; Enoch Obeng; Dongyang Zheng; Jianliang Shen; Zi Jin (Chemical Engineering Journal, 2023)

Evaluation of Cd2+ stress on Synechocystis sp. PCC6803 based on single-cell elemental accumulation and algal toxicological response - Yao Tao; Man He; Beibei Chen; Gang Ruan; Pingping Xu; Yixue Xia; Gaofei Song; Yonghong Bi; Bin Hu (Aquatic Toxicology, 2023)

Depositional processes of the mixed siliciclastic-carbonate system in the Lower Cambrian Xiannüdong Formation in the northern Sichuan Basin, South China - Ting Li; Weiqiang Yang; Chaojin Lu; Pingping Li; Zhehang Xu; Yuan He; Jinbao Duan; Huayao Zou (Marine and Petroleum Geology, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Effects of LED spectrum on circadian rhythmic expression of clock genes and Aanat2 in the brain of juvenile European seabass (Dicentrarchus labrax) - He Ma; Songtao Liu; Pingping Wei; Fan Fei; Jilong Ren; Mingyun Dai; Zhen Ma; Ying Liu (Frontiers in Marine Science, 2023)
The circadian rhythm is a physiological phenomenon that occurs in various organisms with a cycle of about 24 hours. Light is one of the important environmental factors affecting biological rhythm. To clarify whether a shift in light spectrum can influence the circadian expression in fish brain, a total of 175 European seabasses [body weight: 32.5 ± 0.71) g; body length: (13.78 ± 0.35) cm] were exposed to white light (WL), red light (RL), yellow light (YL), green light (GL) or blue light (BL). After 50 days of exposure, circadian expressions of four core clock genes ( Clock, Bmal1, Per2, Cry1 ) and Aanat2 gene in brain were examined. The results showed that the temporal expression patterns of positive clock gens ( Clock and Bmal1 ) showed increases during the scotophase and decreases during the photophase, with peaks near the middle of the darkness. Clock gene expression showed a stable circadian rhythm (R 2 = 0.578-0.824, P =0.000- 0.027) in all light groups while Bmal1 showed circadian rhythm in WL, GL and RL, not in BL and YL. Daily expression patterns of the negative clock genes oscillated in the opposite phase from the positive clock genes, showing increasing mRNA levels during the light, decreases during the dark, and peaks near the shift from night to day, except Per2 in RL and Cry1 in BL. Compared with WL, the acrophases of Clock and Bmal1 were delayed under all light treatments (BL: + 3.7h, +6.73h; RL: +2.4h,+1.35h; YL: + 4.94h, 2.00h; GL: +0.05, +0.16h). Cry1 showed advanced acrophase under all light treatments (BL: -10.74 h, GL: -3.81 h, RL: -3.93 h, YL: -7.56 h) but Per2 showed delayed acrophase in all light treatments (GL: +0.86 h, RL: +10.35 h, YL: +9.62 h), except in BL (-0.43 h). The acrophase of Aanat2 was advanced by all monochromatic light, the Aanat2 level was significantly increased in RL compared with other light treatment. Therefore, the results indicate that RL may regulate the expression of Aanat2 gene by affecting the expression of clock gene in fish brain. Spectrum can affect the biological clock system of fish, and unreasonable spectrum may disturb the rhythm of gene expression of biological clock of fish. Under the irradiation of light spectrum, some clock genes still maintain obvious circadian oscillation, while the rhythm of some clock genes is not obvious and may be destroyed. Our findings suggest a primary role of light spectrum information to the fish brain circadian system.

Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2023)

Cytotoxicity and pro-inflammatory effect of polystyrene nano-plastic and micro-plastic on RAW264.7 cells - Xiaoxia Wang; Xiao-Min Ren; Huan He; Fan Li; Kunqian Liu; Fenqing Zhao; Huixiang Hu; Pingping Zhang; Bin Huang; Xuejun Pan (Toxicology, 2023)

A quantitative analysis of research trends in flood hazard assessment - Wei Zhu; Xianbao Zha; Pingping Luo; Shuangtao Wang; Zhe Cao; Jiqiang Lyu; Meimei Zhou; Bin He; Daniel Nover (Stochastic Environmental Research and Risk Assessment, 2023)

Transcriptomes of Different Tissues for Expression Characteristics Analysis of MYB gene Family in Kenaf (Hibiscus cannabinus L.) - Hu Li; Xin Yang; Sylvain Niyitanga; Qinyao He; Siyuan Chen; Jiantang Xu; Jianmin Qi; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2022)

Identification and Characterization of microRNAs in the Gonads of Litopenaeus vannamei Using High-Throughput Sequencing - Wei Li; Pingping He; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Li Zhang; Bin Zhang; Yusi Zheng; Xin Li; Qingsong He; Longcheng Liu; Chang Yuan; et al. (Fishes, 2022)
Although the expression of miRNAs has been widely applied to investigate on gonads, the role of miRNAs in the gonadal development of white Pacific shrimp (Litopenaeus vannamei) remains unknown. In this study, we performed high-throughput sequencing to identify the sex-related microRNAs (miRNAs) that elucidated the regulatory mechanisms on the gonadal differentiation of L. vannamei. We obtained a total of 29,671,557 and 28,526,942 raw reads from the ovaries and testes library, respectively. We then mapped 26,365,828 (92.73%) of the ovarian clean sequences and 23,694,294 (85.65%) of the testicular clean sequences for a transcriptome reference sequence of L. vannamei. After blasting the miRNA sequences against the miRBase database, we identified 153 significantly differentially expressed miRNAs between the ovaries and testes. To confirm the high-throughput sequencing results, we used a reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) to verify the expression patterns of the seven most differentially expressed miRNAs (i.e., novel_mir23, miR-92b-3p_3, miR-12-5p_2, novel_mir67, miR-279_1, let-7-5p_6, miR-263a-5p_1). According to the results of RT-qPCR, most of the miRNAs were expressed consistently with the high-throughput sequencing results. In addition, the target genes significantly enriched several Kyoto Encyclopedia of Genes and Genome (KEGG) pathways that were closely related to gonadal differentiation and development, including extracellular matrix–receptor interaction, Hedgehog signaling pathway, protein digestion and absorption and cell adhesion molecules (CAMs). This study revealed the first miRNAs sequencing of L. vannamei gonads. We identified sex-related differentially expressed miRNAs and KEGG pathways, which will be helpful to facilitate future research into the regulatory mechanism on the gonadal differentiation of L. vannamei.

Exploring sustainable solutions for the water environment in Chinese and Southeast Asian cities - Pingping Luo; Yong Mu; Shuangtao Wang; Wei Zhu; Binaya Kumar Mishra; Aidi Huo; Meimei Zhou; Jiqiang Lyu; Maochuan Hu; Weili Duan; Bin He; Daniel Nover (Ambio, 2022)

Spatial and temporal variation of dissolved heavy metals in the Lijiang River, China: implication of rainstorm on drinking water quality - Liming Deng; Asfandyar Shahab; He Xiao; Jieyue Li; Saeed Rad; Jinping Jiang; GuoYu; Pingping Jiang; Hongwei Huang; Xiangkui Li; Bilal Ahmad; Jamil Siddique (Environmental Science and Pollution Research, 2021)

Serotonin 2A receptor function and depression-like behavior in rats model of hypothyroidism - Zhicheng Jin; Jianer Ling; Jing Yu; Mengzi He; Pingping Ni; Fang Zhang; Yizhen Wang (Experimental Brain Research, 2021)

Bioavailability of heavy metals bounded to PM2.5 in Xi’an, China: seasonal variation and health risk assessment - Tiantian Wu; Pingping Liu; Xintian He; Hongmei Xu; Zhenxing Shen (Environmental Science and Pollution Research, 2021)

Recent advances in analytical techniques for the detection of adulteration and authenticity of bee products – A review - Ziying Wang; Pingping Ren; Yongning Wu; Qinghua He (Food Additives & Contaminants: Part A, 2021)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

Reactive oxygen species induced by personal exposure to fine particulate matter emitted from solid fuel combustion in rural Guanzhong Basin, northwestern China - Yaqi Li; Hongmei Xu; Kailai He; Jinhui Wang; Zhi Ning; Qiyuan Wang; Nan Li; Zhenxing Shen; Pingping Liu; Jian Sun; Xinyi Niu; Yongxiao Cao; et al. (Air Quality, Atmosphere & Health, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Improving photoelectrochemical reduction of Cr(VI) ions by building α-Fe2O3/TiO2 electrode - Pingping Wang; Faqin Dong; Mingxue Liu; Huichao He; Tingting Huo; Lei Zhou; Wei Zhang (Environmental Science and Pollution Research, 2018)

Crystallization of microporous TiO2 through photochemical deposition of Pt for photocatalytic degradation of volatile organic compounds - Ji Li; Yanhong Wang; Yiyuan Tian; Xuan He; Pingping Yang; Minghui Yuan; Yuqing Cao; Jinze Lyu (Environmental Science and Pollution Research, 2018)

Spatiotemporal variability of Hokkaido's seasonal precipitation in recent decades and connection to water vapour flux - Weili Duan; Bin He; Netrananda Sahu; Pingping Luo; Daniel Nover; Maochuan Hu; Kaoru Takara (International Journal of Climatology, 2017)
Based on 169 stations, annual, seasonal and monthly precipitation trends for the northern Japanese island of Hokkaido were analysed for the period 1980–2011 using the Mann–Kendall test and geostatistical interpolation techniques. Possible association with water vapour flux was explored using ERA ‐Interim reanalysis data. Precipitation increased in Hokkaido over the study period at both the annual and seasonal scales. In general, the northwest had higher precipitation than the southeast in winter, autumn and on an interannual basis and precipitation tended to be concentrated in the southeast in both spring and summer. There was also more precipitation during warm times of the year. For example, precipitation occurred mainly during the summer, ranging from 233 to 751 mm and autumn, ranging from 218 to 724 mm, while precipitation was significantly less in winter and spring. Most stations with declining precipitation trends were located in areas with higher precipitation, such as the west in winter and autumn and the southeast fringe in summer and scattered across the areas with lower precipitation in spring. Increases in precipitation were mainly seen in February, May, June, July, September, November and December at more than 100 stations. Amongst these, almost all of the stations showed positive trends in May (168 stations) and July (165 stations). Finally, the changes of the water vapour transport and budget in whole‐layers between the period 1980–2011 possibly explained the spatiotemporal distribution of precipitation trends in Hokkaido.

Assessment of hydrological extremes in the Kamo River Basin, Japan - Maochuan Hu; Takahiro Sayama; Weili Duan; Kaoru Takara; Bin He; Pingping Luo (Hydrological Sciences Journal, 2017)

Sorption of Sulfadiazine, Norfloxacin, Metronidazole, and Tetracycline by Granular Activated Carbon: Kinetics, Mechanisms, and Isotherms - Pingping Liu; Qiaorui Wang; Chunli Zheng; Chi He (Water, Air, & Soil Pollution, 2017)

Changes of precipitation amounts and extremes over Japan between 1901 and 2012 and their connection to climate indices - Weili Duan; Bin He; Kaoru Takara; Pingping Luo; Maochuan Hu; Nor Eliza Alias; Daniel Nover (Climate Dynamics, 2015)

Anomalous atmospheric events leading to Kyushu’s flash floods, July 11–14, 2012 - Weili Duan; Bin He; Kaoru Takara; Pingping Luo; Daniel Nover; Yosuke Yamashiki; Wenrui Huang (Natural Hazards, 2014)

Geochronologic-petrochemical studies of the Hongshishan mafic–ultramafic intrusion, Beishan area, Xinjiang (NW China): petrogenesis and tectonic implications - Benxun Su; Kezhang Qin; Patrick Asamoah Sakyi; Dongmei Tang; Pingping Liu; Sanjeewa P.K. Malaviarachchi; Qinghua Xiao; He Sun (International Geology Review, 2012)

Olivine compositional mapping of mafic-ultramafic complexes in eastern Xinjiang (NW China): Implications for Cu-Ni mineralization and tectonic dynamics - Benxun Su; Kezhang Qin; He Sun; Dongmei Tang; Qinghua Xiao; Pingping Liu; Patrick Asamoah Sakyi (Journal of Earth Science, 2012)

Bayesian analysis of within-field variability of corn yield using a spatial hierarchical model - Pingping Jiang; Zhuoqiong He; Newell R. Kitchen; Kenneth A. Sudduth (Precision Agriculture, 2009)